1998
DOI: 10.1111/j.1600-0765.1998.tb02350.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical forces alter extracellular matrix synthesis by human periodontal ligament fibroblasts

Abstract: Periodontal ligament fibroblasts (PDLFs) are a heterogeneous population of cells that are involved in the normal maintenance, repair and regeneration of both the ligament and adjacent hard tissues. Additionally, the ability of these cells to respond to mechanical stimulation suggests that they have a central role in mediating the osseous remodeling that underlies physiological and orthodontic tooth movement. To characterize their role further in this process, the current study evaluated the effect of tensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
89
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(95 citation statements)
references
References 29 publications
6
89
0
Order By: Relevance
“…This supports the studies of Howard et al and He et al and suggests that stretching stress facilitates cellular differentiation of PDL cells into osteoprogenitor cells 3,5,19) . It has been demonstrated that mechanical stretching stress may modulate the increase magnitude-dependently of Col-I synthesis in PDL cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This supports the studies of Howard et al and He et al and suggests that stretching stress facilitates cellular differentiation of PDL cells into osteoprogenitor cells 3,5,19) . It has been demonstrated that mechanical stretching stress may modulate the increase magnitude-dependently of Col-I synthesis in PDL cells.…”
Section: Discussionsupporting
confidence: 91%
“…genesis [3][4][5][7][8][9][12][13][14][17][18][19][21][22][23][24][25] , that HSP70 was involved in homeostasis 1,16) , and that bFGF was closely involved in both functions 11,18,20) . Although the magnitude of human bite force varies, 500-3,000 g was selected as the standard force for clinical studies 2) .…”
Section: Discussionmentioning
confidence: 99%
“…8 In general, these two types of stress combine to form the total stress at a particular location. The utility of these classifications is supported by loading experiments on tissues where chondrogenic protein expression in cartilage is up-regulated in response to pressure, 15,22 while structural protein expression is enhanced in fibrous connective tissues in response to distortion. 4,22,23 While the concept that physical factors such as pressure and distortion are involved in tissue modeling and remodeling has become widely accepted, the majority of this evidence has been collected from differentiated cell types or tissue explants.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, direct comparison of our results to those used by other investigators was difficult given the broad range of frequencies (0.0167 Hz, 50 0.25 Hz, 55 and 0.167 Hz…”
mentioning
confidence: 64%